2015
DOI: 10.1039/c4cc06704e
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric core-expanded aza-BODIPY analogues: facile synthesis and optical properties

Abstract: Significantly large Stokes shifts and enhanced solid state emissions were achieved in a novel series of asymmetric core-expanded aza-BODIPY analogues, 4a-4d, synthesized by a facile and scalable two-step reaction in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…[6][7][8][9][10][11] It seems that low-symmetrization of the structures is quite effective to cause more energetically distinguished ground and excited states to enlarge the Stokes shi. 12 However, the synthesis of BOPIM dyes is tedious because of the low synthetic yields. On the other hand, the chemical stability of BOPIM dyes needs to be enhanced because they tend to decompose under basic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] It seems that low-symmetrization of the structures is quite effective to cause more energetically distinguished ground and excited states to enlarge the Stokes shi. 12 However, the synthesis of BOPIM dyes is tedious because of the low synthetic yields. On the other hand, the chemical stability of BOPIM dyes needs to be enhanced because they tend to decompose under basic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the crystal packing of 2 a was confirmed to have a J‐type arrangement, with an interplanar distance of 3.67 Å and a zigzag pattern (Figure a). This type of packing in conjunction with a large Stokes shift tends to minimize self‐absorption (self‐quenching), which leads to the relatively strong fluorescence of 2 a in the solid state. In contrast, the fluorescence maxima of 3 and 4 were not shifted, which indicated that J‐type interactions were not dominant for these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…To generate large Stokes shifts and restrict the planarity of the parent benchmark compounds, many modifications have been introduced, such as the inclusion of special moieties at the (aza)BODIPY core, including bulky groups and tetraphenylethene units, the formation of J ‐aggregates with a meso ‐CF 3 group or spiro‐structures with diaryl or dicarboxylate chelates, asymmetrization of the (aza)BODIPY core, development of new types of asymmetrical BF 2 complexes, such as the replacement of a pyrrole by a pyridine ring, and alteration of ligand through contraction or expansion of its core (Figure ).…”
Section: Introductionmentioning
confidence: 99%